STUDENTS’ TRANSLATION AND ATTITUDE TOWARDS PRACTICE-ORIENTED TRANSLATION IN TEACHING TRANSLATION - Sariasih, Wiwit; Rafli, Zainal; Iskandar, Ifan (Universitas PGRI Sumatera Barat, 2023)
AbstractTeaching translation with practice-oriented is not only focusing on practicing translation the text but also learning how the theory works in translation process. This research aimed to investigate students’ translation and attitude to practice-oriented translation in teaching translation. The samples were the students of English Department of Universitas Pamulang who took Indonesian-English Translation subject. The design of the research was descriptive qualitative research where the data were taken from students’ translation assignment and questionnaire. The translation assignments were analyzed based on bilingual competence; textual competence (cohesive and rhetorical structure). The data from the questionnaire were analyzed based on two indicators; lecturer’s approach and classroom activity. The findings were 1) the first half semester the translations were mostly word-to-word translation that the result was not equivalent enough to the source text, but then at the second half semester the students observed the rhetorical structure and the message of the source text that made their translation equivalent to the source text, 2) students’ attitude toward the practice-oriented translation is positive and, 3) the students translation was considered improve judging from the score that they gained from the first the method was used. Keywords: attitude, practice-oriented, translation